2008
DOI: 10.1292/jvms.70.1305
|View full text |Cite
|
Sign up to set email alerts
|

Recombination Between Vaccine and Field Strains of Canine Parvovirus is Revealed by Isolation of Virus in Canine and Feline Cell Cultures

Abstract: ABSTRACT. Canine parvovirus type 2 (CPV) is a pathogen that causes severe hemorrhagic gastroenteritis with a high fatality rate in pups worldwide. Since CPV emerged in the late 1970s, its origin has been explored with the conclusion that CPV originated from feline panleukopenia virus or a closely related virus. Both high mutation rate and recombination are assumed to be key factors in the evolution of parvoviruses. Here we provide evidence for natural recombination in CPV isolated from dogs in cell culture. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 59 publications
6
43
1
2
Order By: Relevance
“…The XJ-1 strain may be the first recombinant resulting from a crossspecies infection. We believe that the inter-FPV subspecies recombination revealed in the present study, together with the inter-antigenic recombination of CPV recently reported in vaccinated pups [20], should be considered as mechanisms for both the emergence of CPV and the evolution of parvoviruses in nature, in addition to the previous "high mutation & positive selection" theory [32].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The XJ-1 strain may be the first recombinant resulting from a crossspecies infection. We believe that the inter-FPV subspecies recombination revealed in the present study, together with the inter-antigenic recombination of CPV recently reported in vaccinated pups [20], should be considered as mechanisms for both the emergence of CPV and the evolution of parvoviruses in nature, in addition to the previous "high mutation & positive selection" theory [32].…”
Section: Discussionsupporting
confidence: 67%
“…More recently, we provided the first clear evidence of recombination events between CPV antigenic types in natural conditions: that is, between vaccine CPV-2 and field CPV-2a, and vaccine CPV-2 and field CPV-2b viruses, in dogs vaccinated with live combined vaccine containing CPV-2 [20]. These results suggested that recombination is a more frequent event than previously believed for the FPV subspecies that generally cause acute infection.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…XX w. opracowano różne rodzaje szczepionek przeciw chorobom wywołanym przez FPV. Pierwsze szczepionki przeciw chorobom wywołanym przez MEV, CPV opracowano w kilkanaście lat po wystąpieniu pierwszych ognisk chorobowych (24,25,37). Szczepionki te są także stosowane w immunizacji dzikich zwierząt mięsożer-nych i wydają się dla nich bezpieczne oraz skutecznie chronią przed wystąpieniem choroby.…”
Section: Parwowirusy Zwierząt Mięsożernychunclassified
“…Istnieje podejrzenie, że u ko-tów zakażonych CPV, podobnie jak u psów, występują czasami równoczesne zakażenia lokalnymi szczepami oraz wirusami szczepionkowymi (25). Populacja wirusa jest właściwie homogenna, a źródłem zmienności są głównie zakażenia mieszane FPV oraz CPV, co znajduje potwierdzenie w zakażeniu mieszanym in vivo FPV i CPV (39).…”
Section: Zakażenia Mevunclassified